2013
DOI: 10.1037/a0033987
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Five-Factor Model traits and perceived job strain: A population-based study.

Abstract: This study examined the association between Five-Factor Model personality traits and perceived job strain. The sample consisted of 758 women and 614 men (aged 30-45 years in 2007) participating in the Young Finns study. Personality was assessed with the Neuroticism, Extraversion, Openness, Five-Factor Inventory (NEO-FFI) questionnaire and work stress according to Karasek's demand-control model of job strain. The associations between personality traits and job strain and its components were measured by linear r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(67 citation statements)
references
References 46 publications
(96 reference statements)
1
66
0
Order By: Relevance
“…AC candidates are almost always faced with social interaction tasks that are probably more favorably seen by extraverted than introverted individuals. In addition, as extraverts also tend to perceive more control and less strain at work (Törnroos et al, 2013), we believe that extraversion will be positively related to perceptions of the AC that are relevant for negative psychological effects. Furthermore, it was found that extraverts place more importance on different aspects of the selection process than introverts (Viswesvaran & Ones, 2004).…”
Section: Big Fivementioning
confidence: 89%
See 1 more Smart Citation
“…AC candidates are almost always faced with social interaction tasks that are probably more favorably seen by extraverted than introverted individuals. In addition, as extraverts also tend to perceive more control and less strain at work (Törnroos et al, 2013), we believe that extraversion will be positively related to perceptions of the AC that are relevant for negative psychological effects. Furthermore, it was found that extraverts place more importance on different aspects of the selection process than introverts (Viswesvaran & Ones, 2004).…”
Section: Big Fivementioning
confidence: 89%
“…Finally, Truxillo et al (2006) found significant relationships between agreeableness, emotional stability, and openness to experience with justice perceptions of a written multiple-choice selection test used to select police recruits. In addition, less agreeable individuals were shown to perceive less control and more strain at work (Törnroos et al, 2013). Based on the results of the aforementioned studies, we expect that, first, agreeableness will be positively related to applicant perceptions of the AC.…”
Section: Big Fivementioning
confidence: 93%
“…A study conducted by Törnroos et al (2013) highlighted that job strain was positively predicted by N and negatively by E and C. Regarding job satisfaction, the FFM seems an important element to evaluate the dispositional base of job satisfaction, and notably N, E, and C displayed important correlations with professional satisfaction in a number of studies (Judge, Heller, & Mount, 2002). However, according to Judge, Heller, and Mount's meta-analysis, only the relations of N and E with job satisfaction were generalized across studies.…”
Section: The Role Of Personality In Understanding Professional Well-bmentioning
confidence: 99%
“…Two crucial questions are, firstly, which personal characteristics function as risk factors for experiences that are known to affect employee well-being and, secondly, what is the relation between these personal characteristics and characteristics of the job across time. Although some associations have been found between personal characteristics and job characteristics (eg, 3,4,5), their predictive associations are still unclear due to the limited longitudinal research with a full panel design. Knowledge on these predictive associations is needed in order to fully understand how job strain develops from the viewpoint of the individual.…”
mentioning
confidence: 99%